Web Based Video Conference Application for Online Learning Media - Andreuw Vandy Lengkong; Yohakim Benedictus Samponu; Kinzie Feliciano Pinontooan; Joe Yuan Mambu (Fakultas Ilmu Komputer, Universitas Klabat, 2022)
The COVID-19 pandemic has created the need for online learning activities at schools and universities. The use of the video conference application itself is one of the most important alternatives to traditional learning activities. According to researchers, the main issues are the high cost of existing applications and the limitation of access devices. There are three main phases in developing this application: server preparation, application development, and implementation. This application was developed using WebRTC, Jitsi JICOFO, Prosody XMPP server, and Nginx web server. The technical maturity of this study is two, the construction of this application is practical, and the examples are limited to the study and speculative. The purpose of this study is to create a web-based video conferencing application that can be accessed from anywhere without logging in with a web browser alone, has a limited time, and can be attended by over 100 users.